Solid acid catalyzed depolymerization of lignin into value added aromatic monomers - Deepa, Ayillath K.; Dhepe, Paresh Laxmikant (RSC Advances, 2014)
Depolymerization of lignin to produce value-added aromatic monomers has attracted a lot of attention since these monomers can potentially be used as fuel additives (octane enhancers) and in turn can improve the prospects of cellulosic ethanol technology to become economically feasible. Here we show that solid acid catalysts could efficiently convert lignin into value added aromatic monomers with 60% yields and ca. 95% mass balance when depolymerization reactions were carried out at 250 degrees C for 30-120 minutes. We found that the reaction parameters have a remarkable effect on improving the yields.